Comparing the approach of a rigid sphere and a deformable droplet towards a deformable fluid surface - de Villeneuve, V; Aarts, D; Lekkerkerker, H (2006)
We compare the low Reynolds number approach of rigid spheres and deformable droplets of similar sizes towards a deformable fluid interface in a fluid-fluid demixing colloid polymer system. The droplets appear during the final stages of phase separation. A small amount of rigid poly(methyl methacrylate) PMMA spheres is added to the top of the sample when phase separation has (nearly) completed. Both spheres and droplets sediment towards the interface. Far away from the surface the (dimensionless) sedimentation velocity of the droplets is slightly higher (by a factor of ∼ 1.07) than that of the spheres, since the friction experienced by the droplets is slightly reduced by inner fluid circulation. Closer to the surface velocities are strongly reduced and the effective friction increases. Furthermore, the fluid surface becomes distorted at droplet/sphere to surface separations of about one diameter. The droplets strongly deform as well. Surprisingly, the velocities of rigid spheres and droplets converge. We attribute this to an increase of the friction factor of the droplet due to droplet deformation. These data may assist in a better understanding of the transport of matter through interfaces and the process of droplet coalescence. Moreover, the similarity of the drainage of rigid spheres and fluid droplets close to the surface supports the idea that from a theoretical point of view the (simpler) drainage problem for rigid spheres already captures some of the physics. © 2006.